Pengetahuan Tentang Menarche Sebagai Upaya Mengurangi Kecemasan Pada Remaja Putri dalam Menghadapi Menarche - Eva Nurlina Aprilia (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2018)
Background: Menarche is the appearance of menstruation or the first time in young women who is a new experience that is biological and psychological in order to achieve maturity and perfection as a woman. This study aims to obtain a description of the relationship of knowledge level with the level of anxiety in Facing Menarche in young women aged 10 to 12 years in SDN Bantulan, Yogyakarta. Method: The research design is descriptive correlation cross-sectional. Respondents numbered 67 girls, using nonprobability sampling. Result: The results showed that there was a correlation between the level of knowledge with the level of anxiety in the face of Menarche in adolescent girls aged 10 to 12 years in SDN Bantulan, Yogyakarta. The study recommends the need for the provision of health education on menstruation or menstruation to young women as a preparation for the preparation of menarche so as to minimize the level of anxiety in young women.